2008
DOI: 10.1534/genetics.108.093625
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Loss Provokes Multiple Pathways to Apoptosis and Produces Genomic Instability inDrosophila melanogaster

Abstract: Telomere loss was produced during development of Drosophila melanogaster by breakage of an induced dicentric chromosome. The most prominent outcome of this event is cell death through Chk2 and Chk1 controlled p53-dependent apoptotic pathways. A third p53-independent apoptotic pathway is additionally utilized when telomere loss is accompanied by the generation of significant aneuploidy. In spite of these three lines of defense against the proliferation of cells with damaged genomes a small fraction of cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 69 publications
7
94
2
1
Order By: Relevance
“…Secondly, it has been suggested that cell competition could be a mechanism to remove aneuploid cells. 27,28 As there is p53-independent removal of aneuploid cells, 27,28 our findings are consistent with cell competition as the mechanism.…”
Section: /P53supporting
confidence: 87%
See 2 more Smart Citations
“…Secondly, it has been suggested that cell competition could be a mechanism to remove aneuploid cells. 27,28 As there is p53-independent removal of aneuploid cells, 27,28 our findings are consistent with cell competition as the mechanism.…”
Section: /P53supporting
confidence: 87%
“…[22][23][24][25][26] Cell competition may be a means to eliminate certain categories of aneuploid cells. 27,28 Seventy-nine ribosomal protein genes, sixty-six of which are haploinsufficient Minute loci, are distributed throughout the Drosophila genome. 2 Copy number changes to parts of the genome are likely to perturb relative dose of Rp/+ genes, and those that reduce Rp gene dose could be subject to cell competition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Flies carrying eyFLP (Newsome et al 2000) and a chromosome with adjacent inverted FRTs, including the Dc3(FrTr61A5)1A and Dc3(FrTr100E3)1A chromosomes, produce dicentric chromosomes in the cells of the developing eyeantennal disc, resulting in a reduced rate of eclosion (because many die as pharate adults) and adults with small rough eyes (data not shown). This is likely a consequence of the cell death that follows dicentric chromosome breakage (Ahmad and Golic 1999;Titen and Golic 2008). When we tested 49 of the w Sb putative TD chromosomes with eyFLP, all progeny had eyes with a wild-type phenotype, confirming that they no longer carried inverted FRTs.…”
Section: W Hen H J Muller Observed That Terminal Defi-mentioning
confidence: 99%
“…20,21 Studies of Drosophila larval somatic tissues showed that the loss of a single telomere could trigger a spectrum of responses: chromosome end fusions, dicentric chromosome breakage, aneuploidy and other signs of genome instability also associated with dysfunctional telomeres in mammals and yeasts.…”
Section: Retrotransposon Telomeres Must Preserve a Stock Of Transposimentioning
confidence: 99%